Failure of empire : Valens and the Roman state in the fourth century A.D. - Lenski, Noel Emmanuel, 1965- (Joan Palevsky imprint in classical literature., 2002)
Failure of Empire is the first comprehensive biography of the Roman emperor Valens and his troubled reign (a.d. 364-78). Valens will always be remembered for his spectacular defeat and death at the hands of the Goths in the Battle of Adrianople.